Penerapan Model Kirkpatrick dalam Evaluasi Program Pelatihan Kepemimpinan Perempuan di Pusat Pengembangan Sumber Daya Wanita Pasoendan Digdaya - Gouvany, Ayu Laras; Siregar, Herlina; Darmawan, Dadan (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – The purpose of this study was to evaluate how participants responded to the women's Leadership Training Program held by the Pasoendan Digdaya women's Resource Development Center (PPSW) in Lebak regency, Banten. To measure participants ' satisfaction with the training program, this evaluation used the Kirkpatrick reaction Level Model.Method – This study was designed to use descriptive qualitative methods. Data were collected through interviews with 10 trainees. The questionnaire addresses various things, such as the relevance of the material, instructor performance, and training facilities. To determine the level of satisfaction of participants, descriptive was used to analyze the data.Findings – The results indicated that participants were generally satisfied with the training program. The training and consumption schedules have been adjusted to meet the needs of the trainees, and the material presented is considered relevant and applicable. However, the instructor is considered to have strong presentation skills. Additionally, the media and facilities used received positive responses, although there are some suggestions for improvements. Research Implications – Providing women with leadership opportunities significantly advances gender equality by ensuring equal access for both women and men. The findings indicate that while the overall training program effectively meets participants' needs, there is room for improvement in the facilitators' skills and the customization of training materials. It is recommended that PPSW Pasoendan Digdaya enhance facilitator competencies and tailor training content more closely to the specific needs of the participants. This study also highlights the potential for further research into effective teaching methods to bolster women's leadership capabilities.